Innovation, Initiative, and Risk-Taking Courage as the Key to Success in Starting and Managing a Business (A Social Science and Entrepreneurship Journal, 2025)
This article discusses the role of innovation, proactivity, andrisk-taking courage as key factors in building and managing abusiness in the midst of the challenges of the era ofReceived 1 Feb 2025Revised 1 Mar 2025Accepted 20 Mar 2025Available online 1 April 2025globalization and increasingly fierce economic competition.Using a case study of AFD Collection, a fashion business thatsuccessfully survived and thrived during the COVID-19pandemic, this article reviews how implementing productinnovation, digital marketing strategies, and adapting tomarket changes can support business continuity and growth.In addition, this article also explores the importance ofeffective human resource management, optimization ofdigital technology to improve operational efficiency, andcareful planning in dealing with market dynamics. Thefindings in this article provide strategic insights and practicaladvice for entrepreneurs, especially in the face ofuncertainty and challenges in volatile global markets, so asto strengthen their
Keywords: Innovation; Proactivity; Entrepreneurship; DigitalMarketing; Business Strategy